2020
DOI: 10.1038/s41550-020-01214-x
|View full text |Cite
|
Sign up to set email alerts
|

Dust/ice mixing in cold regions and solid-state water in the diffuse interstellar medium

Abstract: Whether ice in cold cosmic environments is physically separated from the silicate dust or mixed with individual silicate moieties is not known. However, different grain models give very different compositions and temperatures of grains. The aim of the present study is a comparison of the mid-IR spectra of laboratory silicate-grains/water-ice mixtures with astronomical observations to evaluate the presence of dust/ice mixtures in interstellar and circumstellar environments. The laboratory data can explain the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 58 publications
6
33
0
Order By: Relevance
“…Analysis of cometary dust particles and laboratory analogues of cosmic dust grains; and evolutionary models of dust grains lead to this conclusion (see [280] and references therein).…”
Section: Dust/ice Mixturesmentioning
confidence: 89%
See 2 more Smart Citations
“…Analysis of cometary dust particles and laboratory analogues of cosmic dust grains; and evolutionary models of dust grains lead to this conclusion (see [280] and references therein).…”
Section: Dust/ice Mixturesmentioning
confidence: 89%
“…Experimental studies of dust/ice mixtures are a new direction of research pioneered by one of the authors of this review [49,50,280,281]. Some results, on desorption of H2O and CO mixed with carbon and silicate grains and on the photochemistry of carbon grains/H2O ice mixtures, have been already discussed in Sections 6.3 and 7.2.…”
Section: Dust/ice Mixturesmentioning
confidence: 97%
See 1 more Smart Citation
“…Despite the challenges, new laboratory data combining ice and dust could provide a better understanding of the link between ice and dust in star-forming regions. To this end, Potapov et al (2018Potapov et al ( , 2021 measured spectrum and optical constants of silicate (MgSiO 3 ) and H 2 O ice, and showed that this experimental data can partially fit the 3 µm of some astronomical objects.…”
Section: Silicate Removalmentioning
confidence: 99%
“…Despite the challenges, new laboratory data combining ice and dust could provide a better understanding of the link between ice and dust in star-forming regions. With this goal, Potapov et al (2018Potapov et al ( , 2021 have measured spectrum and optical constants of silicate (MgSiO 3 ) and H 2 O ice, and showed that this experimental data can partially fit the 3 µm of some astronomical objects.…”
Section: Silicate Removalmentioning
confidence: 99%